Intercropping Technique at a Smallholder Oil Palm Plantation in Mancang Village, Langkat, North Sumatra - Muhdi; Sahar, Asmarlaili; Safni, Irda; Hanafiah, Diana Sofia (Talenta Publisher, 2022)
Oil palm plantations have become an international issue as a cause of land conversion and deforestation for agricultural expansion. Utilization of land for oil palm plantations is appropriate to provide benefits to the community and residents around the plantation companies as well as to the plantation companies. Mitra, is the owner of an oil palm plantation with his address at Kwala Begumit, Langkat, North Sumatra. The area of oil palm plantations is about 6 hectares. The food crops grown are intercropped on smallholder oil palm plantations in Mancang Village, Kec. Done, District. Binjai, North Sumatra in the implementation of community service is soybean [Glycine max (L) Merr] Anjasmoro variety. In general, the implementation of service activities in the form of counseling, discussions, demonstrations and planting soybeans [Glycine max (L) Merr] Anjasmoro variety intercropped on oil palm plantations can run very well. Based on the existing problems, it is necessary to develop this activity by being carried out in communities related to smallholder oil palm plantations.